Sets and proofs : invited papers from Logic Colloquium '97, European Meeting of the Association for Symbolic Logic, Leeds, July 1997 - Cooper, S. B. (S. Barry); Truss, J. K. (London Mathematical Society lecture note series, 1999)
Together, Sets and Proofs and its sister volume Models and Computability will provide readers with a comprehensive guide to mathematical logic. All the authors are leaders in their fields and are drawn from the invited speakers at 'Logic Colloquium '97' (the major international meeting of the Association of Symbolic Logic). It is expected that the breadth and timeliness of these two volumes will prove an invaluable and unique resource for specialists, post-graduate researchers, and the informed and interested nonspecialist.